2010
DOI: 10.1021/jz1000819
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Architecture in Organic Photovoltaic Cells

Abstract: What are the stumbling blocks for achieving high-efficiency organic photovoltaic devices? This question is examined from a molecular architecture and molecular packing perspective. The intermolecular interaction between the electron donor and electron acceptor influences the charge separation. The packing of electron donors and acceptors influences the charge transport. Therefore, there is a need to strike a balance between the chargetransfer interactions and packing interactions and obtain nanoscale segregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 69 publications
1
123
0
Order By: Relevance
“…It is now well understood that there are three factors that concurrently facilitate the formation of a BHJ in the P3HT-PCBM system. 3,49,50 These are (1) the propensity of P3HT to rapidly crystallize in the presence of PCBM, (2) the large diffusion coefficient of PCBM in amorphous P3HT and (3) the slow kinetics of crystallization of PCBM in the presence of P3HT. It is noteworthy that the HR TEM images reported by Russell and coworkers 49 also show that the interface between PEDOT/PSS and P3HT becomes stronger after the annealing process.…”
Section: Morphologies In Opv Active Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well understood that there are three factors that concurrently facilitate the formation of a BHJ in the P3HT-PCBM system. 3,49,50 These are (1) the propensity of P3HT to rapidly crystallize in the presence of PCBM, (2) the large diffusion coefficient of PCBM in amorphous P3HT and (3) the slow kinetics of crystallization of PCBM in the presence of P3HT. It is noteworthy that the HR TEM images reported by Russell and coworkers 49 also show that the interface between PEDOT/PSS and P3HT becomes stronger after the annealing process.…”
Section: Morphologies In Opv Active Layersmentioning
confidence: 99%
“…[3][4][5] The photons are absorbed by the conjugated polymer, which creates excited electron-hole pairs. These electronhole pairs, excitons, either recombine to emit light or heat or, in a more useful process, dissociate and move to their respective electrodes to result in a photovoltaic current.…”
Section: Introductionmentioning
confidence: 99%
“…% PCBM, indicating that PCBM is macroscopically phase-separated upon annealing where electrons may easily be trapped in PCBM domains. 14,15 Comparison of charge mobility of an unannealed device with that of an annealed one indicates that annealing does not enhance charge mobility for amorphous conjugated polymer P(3HT-MeTDQ).…”
Section: B Charge Transport In Low Bandgap Polymermentioning
confidence: 99%
“…These values are dependent strongly on photophysical properties of specific D/A material and its blending morphology. [14][15][16] However, phase behavior at molecular levels, including spatial arrangement of amorphous polymeric chain/fullerene in blends, has still been far from a complete understanding due to its complex nature. In 2008, two research groups reported the binary phase diagrams of semicrystalline poly(3-hexyl thiophene) (P3HT)/ PCBM blends 17 and amorphous poly(phenylene vinylene) (PPV) derivative/PCBM.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, many efforts have been made to clarify low-energy green emission bands (also called g-bands) in PF-based electroluminescent thin films for application in high-performance devices [86]. Organic nanosystems from fully conjugated block copolymers offer a new solution for solar cells [87,88]. Self-assembly of p-n fully conjugated diblock copolymers can achieve nanostructured thin films with two ordered independent channels of electrons and hole.…”
Section: Introductionmentioning
confidence: 99%